Schaum's outlines Russian grammar - Levine, James S. 1949- (Schaum's outline series, 2018)
Fortunately, there's Schaum's. This all-in-one-package includes more than 220 practice exercises to sharpen your grammar skills. You'll find everything you need to build confidence, skills, and knowledge for the highest score possible. More than 40 million students have trusted Schaum's to help them study faster, learn better, and get top grades. Now Schaum's is better than ever-with a new look, a new format with hundreds of practice problems, and completely updated information to conform to the latest developments in every field of study. Schaum's Outline of Russian Grammar, Third Edition features: Grammatical expressions used by native Russian speakers today A complete review of grammar rules An accessible format for quick and easy review Hundreds of example sentences, and more Access to revised Schaums.com website